Aldersgate and Athens John Wesley and the Foundations of Christian Belief - Abraham, William J. (William James) (Waco Baylor University Press, 2010)
In this day, John Wesley offered important insights on how to obtain knowledge of God that readily bears fruit in our own times. As premiere Wesleyan scholar William Abraham shows, Wesley's most famous spiritual experience is rife with philosophical significance and implications.
The material that follows represents the substance of a series of lectures delivered at Barker Road Methodist Church in Singapore --Pref.
Keywords: Wesley, John, -- 1703-1791. Conversion -- Christianity -- Case studies. God -- Knowableness. Faith. Conversion -- Christianity